2015
DOI: 10.1128/jvi.02933-14
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 Engineered To Contain MicroRNA Targets for Muscle-Specific MicroRNAs Displays Attenuated Cardiotropic Virulence in Mice

Abstract: Coxsackievirus B3 (CVB3) is trophic for cardiac tissue and is a major causative agent for viral myocarditis, where local viral replication in the heart may lead to heart failure or even death. Recent studies show that inserting microRNA target sequences into the genomes of certain viruses can eradicate these viruses within local host tissues that specifically express the cognate microRNA. Here, we demonstrated both in vitro and in vivo that incorporating target sequences for miRNA-133 and -206 into the 5= untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
(40 reference statements)
2
29
1
Order By: Relevance
“…The genomic structure of picornaviruses can be divided into a 5′‐UTR, the protein coding region, and a 3′UTR, and previously it was shown that CVB3 with miR‐TS in the 5′‐UTR and in the 3′UTR are susceptible to their corresponding miRs . On the other hand, it has also been shown that certain sections within the 5′‐UTR and 3′UTR do not tolerate miR‐TS insertion, most likely because insertion of miR‐TS disturbed higher‐order RNA structures of the viral genome . In the present study, we pursued a new approach and inserted the miR‐375TS into the 5′ terminus of the polyprotein coding region of the CVB3 genome and compared it to insertion immediately downstream of the polyprotein stop codon in the 3′UTR, which is known to tolerate miR‐TS .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The genomic structure of picornaviruses can be divided into a 5′‐UTR, the protein coding region, and a 3′UTR, and previously it was shown that CVB3 with miR‐TS in the 5′‐UTR and in the 3′UTR are susceptible to their corresponding miRs . On the other hand, it has also been shown that certain sections within the 5′‐UTR and 3′UTR do not tolerate miR‐TS insertion, most likely because insertion of miR‐TS disturbed higher‐order RNA structures of the viral genome . In the present study, we pursued a new approach and inserted the miR‐375TS into the 5′ terminus of the polyprotein coding region of the CVB3 genome and compared it to insertion immediately downstream of the polyprotein stop codon in the 3′UTR, which is known to tolerate miR‐TS .…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐mediated virus detargeting represents a powerful technique to prevent oncolytic viruses from replicating in nontargeted tissues, which makes this technique a valuable approach to increase the safety of this type of cancer therapy . Addressing prevention of undesirable CVB3 replication in the heart by insertion of muscle‐specific miR‐206TS and miR‐133TS has been carried out successfully , whereas attenuation of CVB3 in the pancreas and heart was achieved by insertion of miR‐34aTS into the CVB3 genome .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, molecular mechanisms of RMS development have still not been fully elucidated . In this regard, identification of crucial biomarkers can improve our understanding of RMS tumour biology and help us discover novel targets for its therapy in clinical settings .…”
Section: Introductionmentioning
confidence: 99%